Optimality conditions and duality for multiobjective semi-infinite programming with data uncertainty via Mordukhovich subdifferential - Pham, Thanh-Hung (Yugoslav Journal of Operations Research, 2021)
Based on the notation of Mordukhovich subdifferential in [27], we propose some of new concepts of convexity to establish optimality conditions for quasi ε−solutions for nonlinear semi-infinite optimization problems with data uncertainty in constraints. Moreover, some examples are given to illustrate the obtained results. This article has been corrected. Link to the correction 10.2298/YJOR211117025E